First report card on physical activity for children and adolescents in Slovakia: a comprehensive analysis, international comparison, and identification of surveillance gaps - Peter Bakalár; Lenka Hnidková; Beáta Ružbarská; Pavel Ružbarský; Terézia Kovalik Slančová; Jaroslava Kopčáková; Michaela Kostičová; Aleš Gába (BMC, 2024)
Abstract Background National surveillance of physical activity (PA) is essential to establish public health policy actions for PA promotion and evaluation, thereby promoting accountability. The main goal of this study is to comprehensively analyse surveillance data on PA behaviours, outcomes, and influencing factors among Slovakian children and adolescents by using the methodology of the Active Healthy Kids Global Alliance Global Matrix (AHKGA-GM) project. Secondary goals are to provide comparisons with international data and the identification of surveillance gaps. Methods A comprehensive multilevel search strategy for data about 10 core indicators and 1 additional indicator published between 2015 and 2020 (solely pre-COVID-19-pandemic data) was used. The data were then synthesised, and a set of standardised benchmarks was used to assign grades according to The Global Matrix 4.0 Grading Rubric. Results A total of 552 potentially relevant data resources were retrieved, of which 34 were identified as eligible for data extraction. Grade B was assigned to four core indicators, grade C to five core indicators, and grade D to one core indicator. The additional Sleep indicator was graded a C-. Compared with the average grades from countries with high Human Development Index scores, Slovakia received higher grades in five core indicators (Overall Physical Activity, Active Transportation, Sedentary Behaviours, School, Government), and in the aggregate Behavioural average and Overall average. Compared with global averages, Slovakia had higher grades in the aforementioned core and aggregate indicators, and in the Community and Environment core indicator and aggregate Sources of Influence average indicator. Numerous surveillance gaps were identified. Conclusions The overall grading of the available surveillance data suggests the need for improvement in all 10 surveilled core indicators, and in additional Sleep indicator. Despite the fact that numerous identified surveillance gaps limit the overall informative value of the current grade, they provide the important information needed to enhance surveillance of PA-related indicators in Slovakia. For instance, the focus should be put on younger children and parents, on obtaining the device-measured data on various movement behaviours, on the topic of outdoor physical activities, and policy evaluation.